2020
DOI: 10.1039/c9cp06614d
|View full text |Cite
|
Sign up to set email alerts
|

The role of an unintentional carbon dopant in resolving the controversial conductivity aspects in BiFeO3

Abstract: The electronic structure and properties of carbon incorporated BiFeO3, and resolution to the conductivity aspects of BiFeO3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…The bandgap obtained using the GGA+ U formalism without SOC is 2.48 eV, which is quite close to the experimental value (2.6–2.7 eV). 57,58 The inclusion of SOC leads to the splitting of the band at M , and thus, the CBm is shifted to a point 0.049 Å −1 away from M towards K along with a decrease in the bandgap, indicating the importance of heavy-atom-induced SOC in the calculations. An anisotropic splitting of the band is observed around point M (as shown in the inset of Fig.…”
Section: Electronic Properties and Rashba–dresselhaus Splittingmentioning
confidence: 93%
“…The bandgap obtained using the GGA+ U formalism without SOC is 2.48 eV, which is quite close to the experimental value (2.6–2.7 eV). 57,58 The inclusion of SOC leads to the splitting of the band at M , and thus, the CBm is shifted to a point 0.049 Å −1 away from M towards K along with a decrease in the bandgap, indicating the importance of heavy-atom-induced SOC in the calculations. An anisotropic splitting of the band is observed around point M (as shown in the inset of Fig.…”
Section: Electronic Properties and Rashba–dresselhaus Splittingmentioning
confidence: 93%
“…The nature of conductivity in BiFeO 3 (BFO), whether p-type or n-type, is quite controversial and may be altered by introducing various defects and dopants. In our recent work, carbon is found to be a possible extraneous factor for causing p-type conductivity in BiFeO 3 [2]. Because of the small ionic radius (∼ 0.2-0.4 Å) [6], an H atom is more likely to occupy interstitial sites in BFO.…”
Section: Introductionmentioning
confidence: 91%
“…Incorporation of elements like Hydrogen (H), Lithium (Li), Carbon (C) during material fabrication is quite evident owing to small radii (H and Li) and ubiquitous nature (C) [1][2][3]. The most abundant source of H is the presence of H 2 gas and humidity (H 2 O) in the stratosphere.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that the two elements Fe and Bi in the surface of the wool-BFO composites are covered by a thick layer of TiO 2 , which is in conwith the EDX mapping and TEM observation. When wool flakes are ground with BFO nanosheets under vacuum freeze-drying conditions, besides the sub-peaks of C-H/ C-C, C-N, C-O, C=O and N-C=O in the C1s core-level XPS spectra of wool flakes (figure S4(a)), a new sub-peak at 283.27 eV in the wool-BFO composites is probably attributed to the binding energy of C-Fe/C-Bi (figure S4(e)), which results in p-type conductivity in BFO [66]. It was demonstrated that the Bi and Fe cation vacancies could lead to the introduction of acceptor-type defect levels in the band gap of BFO [66].…”
Section: Chemical Bonding Statesmentioning
confidence: 99%
“…When wool flakes are ground with BFO nanosheets under vacuum freeze-drying conditions, besides the sub-peaks of C-H/ C-C, C-N, C-O, C=O and N-C=O in the C1s core-level XPS spectra of wool flakes (figure S4(a)), a new sub-peak at 283.27 eV in the wool-BFO composites is probably attributed to the binding energy of C-Fe/C-Bi (figure S4(e)), which results in p-type conductivity in BFO [66]. It was demonstrated that the Bi and Fe cation vacancies could lead to the introduction of acceptor-type defect levels in the band gap of BFO [66]. For the N1s core-level XPS spectra, the N-H sub-peak of wool flakes (figure S4(b)) disappears and two new sub-peaks at the binding energies of 397.42 eV (N−Fe) and 398.57 eV (N−Bi) (figure S4(f)) [67] are fitted.…”
Section: Chemical Bonding Statesmentioning
confidence: 99%